Auto-inflammatory challenge of the endolymphatic sac – Cochlear damage measured by distortion product oto-acoustic emissions. (August 2015) - Larsen, Michael; Friis, Morten; Karlsen, Charlotte Vestrup; Poulsen, Steen Seier; Lund, Søren Peter; Qvortrup, Klaus
Abstract Conclusion: Twenty-five rats were challenged by an immunologic attack of the endolymphatic sac. After 6 months, distortion product oto-acoustic emissions (DPOAE) revealed a dysfunction of the outer hair cells and immunological active cells were observed in the endolymphatic sac. This information could contribute to the understanding of Ménière's disease. Objectives: This study investigated if an autoimmune challenge of the endolymphatic sac could affect DPOAE output measurements in rats. Also, a potential autoimmune cell infiltration of the endolymphatic sac was investigated. Methods: Eighteen Lewis rats were immunized with a crude endolymphatic sac extract in complete Freund's adjuvant. Seven control animals were injected with Freund's adjuvant in saline. Cochlear damage was estimated by DPOAE dynamics 3 weeks and 6 months after the immunization. Infiltrative cells in the endolymphatic sac were investigated with transmission electron microscopy. Results: The hearing assessment 6 months after immunization revealed a reduction of the DPOAE, on the full range of frequencies (2–63 kHz) in an average of the mean, of 2 dB ± 1.1 in the immunized group compared to the controls (p < 0.05). The same test showed a 2.5 dB decrease from 2 to 5 kHz (p < 0.01). Immunological active cells were observed in the endolymphatic sac in most of the immunized rats.